A standardized MRI phantom for dissolved phase 129Xe MRI - Max Filkins; Arthur Harrison; Guilhem J. Collier; Graham Norquay; Jim M. Wild; Sean P. Rigby; Galina E. Pavlovskaya; Thomas Meersmann (Journal of Magnetic Resonance Open)
Pulmonary MRI of hyperpolarized xenon-129 (hp129Xe) dissolved in the lung parenchyma and vascular phase is gaining increasing attention for clinical assessment of gas exchange in multiple diseases. These conditions can involve thickening of barrier tissues due to fibrotic scarring or reduced capillary blood flow leading to diminished gas-blood exchange hence, the ratios between hp129Xe signals arising from the lung membrane (M), the red blood cells (RBC), and the gas phase hold significant diagnostic value. However, comparing hp129Xe signal ratios quantitatively across different studies may pose challenges due to varied experimental conditions and opted pulse sequence protocols.A solution to this problem arises from materials science applications of hp129Xe where xenon dissolved in porous materials or polymers can display chemical shifts similar to the M and RBC shift in lungs. This work explored the generation of MR spectral profiles with respect to chemical shift and signal intensity ratios that closely resemble spectral profiles observed in human lungs in health and disease. At ambient temperatures, reticulated open cell polyurethane foam treated with olive oil as a fatty phase produced dissolved phase 129Xe chemical shifts of 215 ppm and 196 ppm, respectively, that emulate typical RBC and M signals. The uptake kinetics into the non-toxic materials was sufficiently similar to pulmonary signal uptake to enable hp129Xe MRI with dissolved phase ratios that closely resembled clinical data.A phantom assembly was devised to allow for gas handling protocols that matched clinical protocols. The current iteration of the developed phantom enables rapid testing of basic experimental protocols and can be used for training purposes without regulatory approval and governance. Furthermore, the introduced concept shows a pathway for the development of a quantitative universal phantom standard for dissolved phase pulmonary hp129Xe MRI. A robust phantom standard will require materials with longer shelf lifetime than the oil-foam system used in this study and would benefit from a hierarchical porous network with more defined microstructure similar to that found in lungs.